Influence of filament patterning in structural properties of dense alumina ceramics printed by robocasting - Baltazar, J. (2021)
Robocasting is an extrusion-based additive manufacturing (AM) technique, highly explored in the fabrication of porous structures or thin-walled ceramics. Comparing to other slurry-based AM technologies, robocasting presents a high potential to produce dense bulk ceramics, thanks to the low organic binder contents and high solids loading used in the feedstock. Despite these benefits, the robocasting fabrication of ceramics with similar mechanical performance as those produced by traditional methods remains a challenge. The goal of this work is to fine-tune the robocasting printing process of dense alumina ceramics by evaluating the influence of in-fill filaments orientation and the medium where the deposition process occurs (air or paraffin bath), on defects and mechanical performance of the sintered parts. Relative density, shrinkage, three-point flexural strength, Young's modulus and hardness were analysed. The specimens with the highest performance were sintered at 1550 °C or 1600 °C temperatures for 2 h holding time and the results were compared with slip casting (SC) samples sintered in the same conditions. Alumina robocasting samples, printed longitudinally in air with controlled humidity and sintered at 1600 °C, exhibited relative density ≈99% with flexural strength (≈350 MPa), Young's modulus (≈366 GPa) and hardness (≈17 GPa) values comparable to those obtained for SC samples. Numerical modelling and simulation were used to analyse the experimental values and the anisotropic behaviour of the printed specimens. Experimental Young's modulus results were compared with the Voigt-Reuss bound and the Hashin-Shtrikman upper-bound, as well as the analytical predictions of a Mooney-type exponential relation.